2020
DOI: 10.1186/s42409-020-00016-1
|View full text |Cite
|
Sign up to set email alerts
|

An English-language adaptation of the Interpersonal Trust Short Scale (KUSIV3)

Abstract: The Interpersonal Trust Short Scale—the English-language adaptation of the Kurzskala Interpersonelles Vertrauen (KUSIV3)—measures interpersonal trust as a psychological disposition with just three items (completion time ~ 30 s). The items of the German-language source version were translated into English using the TRAPD approach. Our empirical validation based on a heterogeneous quota sample in the UK shows that all the reliability coefficients of the English-language adaptation and its correlations with exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 74 publications
0
9
0
2
Order By: Relevance
“…Revising the conceptualization of Adorno et al (1950), Altemeyer (1981) proposed three sub-dimensions of authoritarianism: authoritarian aggression, authoritarian submission, and conventionalism. Although authoritarianism is multidimensional, it has mostly been used as a unidimensional construct (Nießen et al, 2019). However, recent studies have shown that such a strong focus on authoritarianism as a superordinate construct cannot account for peculiarities in the subdimensions of authoritarian attitudes (Clarke et al, 2021; Duckitt et al, 2010; Duckitt and Bizumic, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Revising the conceptualization of Adorno et al (1950), Altemeyer (1981) proposed three sub-dimensions of authoritarianism: authoritarian aggression, authoritarian submission, and conventionalism. Although authoritarianism is multidimensional, it has mostly been used as a unidimensional construct (Nießen et al, 2019). However, recent studies have shown that such a strong focus on authoritarianism as a superordinate construct cannot account for peculiarities in the subdimensions of authoritarian attitudes (Clarke et al, 2021; Duckitt et al, 2010; Duckitt and Bizumic, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The 3-item Interpersonal Trust Short Scale (KUSIV3) [ 56 ]/Kurzskala Interpersonelles Vertrauen [ 15 ] measures a person’s expectation that other persons and institutions can be relied on. KUSIV3 shows sufficient internal consistency (ω = .69 for the English-language version, ω = .75 for the German-language version) and evidence for factorial and construct validity [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…) The extra-short form of the Big Five Inventory-2 (BFI-2-XS; English version:Soto & John, 2017; German version: Rammstedt et al, 2020) b) The General Self-Efficacy Short Scale-3 (GSE-3;(Doll, E. S., Nießen, C., Schmidt, I.,Rammstedt, B., & Lechner, C. M.: The General Self-Efficacy Short Scale-3 (GSE-3): An English-language adaptation, in preparation))/Allgemeine Selbstwirksamkeit Kurzskala (ASKU; Beierlein, Kovaleva, et al, 2014) c) The Internal-External Locus of Control Short Scale-4 (IE-4; (Nießen, D., Schmidt, I., Groskurth, K., Rammstedt, B., & Lechner, C. M.: An Englishlanguage adaptation of the Internal-External Locus of Control Short Scale-4 (IE-4), in preparation))/ Internale-Externale-Kontrollüberzeugung-4 (Kovaleva et al, 2014) d) The Optimism-Pessimism Short Scale-2 (SOP2; (Nießen, D., Groskurth K., Kemper, C. J., Rammstedt, B., & Lechner, C. M.: An Englishlanguage adaptation of the Optimism-Pessimism Short Scale-2 (SOP2), in preparation))/Skala Optimismus-Pessimismus-2 (Kemper, Beierlein, Kovaleva, et al, 2014) e) The Interpersonal Trust Short Scale (KUSIV3; Nießen, Beierlein, et al, 2020)/KurzskalaInterpersonelles Vertrauen(Beierlein, Kemper, et al, 2014a) f) The General Life Satisfaction Short Scale (L-1;Nießen, Groskurth, Rammstedt, et al, 2020)/ Kurzskala zur Erfassung der Allgemeinen Lebenszufriedenheit(Beierlein et al, 2015) g) The political Left-Right Self-Placement scale (English and German versions: Breyer, 2015) h) The Authoritarianism Short Scale (KSA-3;Nießen, Schmidt, et al, 2019)/Kurzskala Autoritarismus(Beierlein, Asbrock, et al, 2014) i) The Justice Sensitivity Short Scales-8 (JSS-8;(Groskurth, K.,Nießen, D., Beierlein, C., Baumert, A., Rammstedt, B., & Lechner, C. M.: An English-Language Adaptation and Validation of the Justice-Sensitivity-Scales-8 (JSS-8), in preparation))/ Ungerechtigkeitssensibilität-Skalen-8 (USS-8;Beierlein, Baumert, et al, 2014) j) The Social Desirability-Gamma Short Scale(KSE- G;Nießen, Partsch, et al, 2019)/Kurzskala Soziale Erwünschtheit-Gamma…”
unclassified